Data files for survey into 'Attitudes towards digital culture and technology in the Modern Languages' - Spence, Paul; Brandao, Renata (King's College London, 2019)
This dataset includes the results of a survey carried out in 2018, the first in a series of landscaping exercises cataloguing interactions between digital culture and modern languages. The survey analyses the impact of ‘digital’ on modern languages across a wide range of factors, including: general digital engagement; digital methods/platforms; digital literacies/pedagogies; and experiences with digital publishing/digital research materials. It captures views from people involved in modern (foreign) languages in various ways (including roles as researcher, learner, teacher, funder, policy-maker, digital practitioner, cultural practitioner or other). Data was submitted randomly, and has been lightly edited to remove any possible identifying features. The response order has also been re-arranged for each question to make it impossible to identify the responses of individuals, again, to avoid identification of respondents. In a few cases we provide extra analysis in addition to the source data, to show our methods in curating the data for analysis. The survey report, published separately from this data, contains further information.
Keywords: Modern languages; Digital culture; Digital humanities